Respuesta :

Answer:

Step-by-step explanation:

Asymptotes 3

g(x) = [tex]\frac{3x}{x^2-3x-10}[/tex]

Factors of denominator will be,

x² - 3x - 10 = x² - 5x + 2x - 10

                 = x(x - 5) + 2(x - 5)

                 = (x + 2)(x - 5)

Therefore, factored form of g(x) will be,

g(x) = [tex]\frac{3x}{(x + 2)(x - 5)}[/tex]

Asymptotes 4

h(x) = [tex]\frac{(x-5)}{x^{2} + 14x + 40}[/tex]

      = [tex]\frac{x-5}{x^{2}+10x+4x+40}[/tex]

      = [tex]\frac{x-5}{x(x+10)+4(x+10)}[/tex]

      = [tex]\frac{x-5}{(x+10)(x+4)}[/tex]

ACCESS MORE